Upaya Digitalisasi melalui Pendampingan Pembuatan Akun Instagram untuk Usaha UMKM Kopi Heloo - Bintang, Abbin Mutiara; Rahmadan, Noval Syabirin; Alfajri, Octo; Peranata, Suria; Hasanah, Uswatun (Pakis Journal Institute, 2025)
Digitalization is crucial for MSMEs as key drivers of the local economy. This study explores how assisting the